Palu-Koro fault on social media: mixed approach study of disaster information spread and the potential of geotourism promotion - Ilyas Lampe; Dyah Fitria Kartika Sari; Putri Limiyanto; Gemilang Bayu Ragil Saputra (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article discusses the role of influencers, social media, and information spread in promoting the geotourism of the Palu-Koro Fault. As one of the governmental bodies responsible for geotourism, the Central Sulawesi Provincial Tourism and Creative Economy Office is trying to introduce these relatively new geotourism sites. One of the efforts is to make full use of social media. Influencers are collaborated with not only to introduce geotourism but also to build branding. Geotourism is one of the many topics brought up by social media users regarding the post-disaster recovery efforts in Pasigala. Thus, in this study, we applied a mixed-method analysis by comparing the analysis of the data collected from Twitter using a descriptive quantitative approach utilising structural and actor-based social network analysis and in-depth interview data with key informants from the Central Sulawesi Provincial Tourism and Creative Economy Office staffs and three influencers in collaboration using descriptive qualitative-case study approach utilising narrative analysis. The results showed that most Twitter users sought prominent actors, such as influencers and government officials, for information in time and after the disaster struck. While the three disasters are the most heavily discussed, post-disaster programs and plans are also prominent, including geotourism. The Central Sulawesi Provincial Tourism and Creative Economy Office collaborated with the influencers due to their ability and potential to spread information fast and wide to their followers. The message is formed to promote the newly formed geotourism sites, educate people, and build positive views of the impacted sites.